The influence of coccygeal dynamic patterns on ganglion impar block treatment results in chronic coccygodynia - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (SAGE PUBLICATIONS INC, 2018)
Objective: Ganglion impar block (GIB) can be performed in patients with chronic coccygodynia who do not respond to conservative treatments. We investigated the effect of coccygeal dynamic patterns on the treatment outcome in patients with chronic coccygodynia treated with GIB. Materials and methods: We retrospectively analyzed the data for patients diagnosed with chronic coccygodynia who underwent GIB only once by a transsacrococcygeal method under fluoroscopy guidance in our Pain Medicine Clinic. Patients were assessed with standard and dynamic coccyx radiographs and classified according to coccygeal mobility. Pain scores were assessed with a numerical rating scale (NRS) before and after the intervention (at 1 hour and 4, 12 and 24 weeks). A 50% or more reduction in the NRS score was accepted as significant pain relief. Results: Of the 37 patients included in the study, 14 had normal coccyx (Group I) and 23 had immobile coccyx (Group II) based on the radiological evaluation. The NRS scores were significantly reduced in both groups on each follow-up visit but there was no significant difference between the two groups in terms of pre- and post-intervention NRS scores. Significant pain relief was achieved in 42.9% and 61.9% of patients in Group I and II at the last examination, respectively. Conclusion: GIB administered by transsacrococcygeal method in patients with chronic coccygodynia is a safe and alternative treatment approach with reduced pain scores and low complication rates. In patients with chronic coccygodynia, having a normal or immobile coccyx does not appear to affect treatment outcomes.
Keywords: Dynamic coccyx X-ray films; coccygodynia; coccydynia; pain management; ganglion impar block; BODY-MASS INDEX; IDIOPATHIC COCCYGODYNIA; SITTING POSITION; COCCYDYNIA; ETIOLOGY; ANATOMY